Effects of seated Tai Chi Yunshou on upper limb function among stroke patients in the subacute phase: A study protocol for a randomized controlled trial - Xinglai Zhang; Chen Chen; Shaohua Chen; Zhenzhen Ma; Hang Gao; Jiayi Ren; Yuanjia Gu; Weijia Gu; Zhenkun Gao; Guo Lu; Jiming Tao (PLoS ONE, 2025)
Background Upper limb dysfunction after stroke is one of the common problems. Tai Chi Yunshou exercise and seated Tai Chi exercise have been confirmed that it is beneficial on upper limb function for stroke patients. Seated Tai Chi Yunshou exercise easier and suitable for stroke patients who are unable to stand. The purpose of this experiment is to explore the effects of seated Tai Chi Yunshou exercise on the upper limb function for stroke patients. Methods 84 stroke patients with upper limb dysfunction were randomly divided into two groups. The experimental group and the control group consist of 42 patients each. The experimental group will receive seated Tai Chi Yunshou training combined with conventional treatment, while the control group only will receive conventional training. Each training session will be implemented once a day and five times per week in a duration of 4 weeks. Primary and secondary outcomes will be measured at baseline and 4-weeks, 8-week follow-up after randomization. Fugl-Meyer Upper Extremity Assessment (FMA-UE) will be the primary outcome and Modified Trunk Impairment Scale (mTIS),the Wolf Motor Function Test (WMFT), Functional near-infrared spectroscopy (fNIRS), Barthel Index(BI) will be the secondary outcome. Functional near-infrared spectroscopy(fNIRS) will be used to explore the therapeutic mechanism. Discussion According to previous studies, Tai Chi Yunshou exercise and tailored seated Tai Chi are effective treatment for stroke patients. In this study, we will conduct a seated Tai Chi Yunshou exercise for patients with stroke. We believe that this study may prove the effectiveness of seated Tai Chi Yunshou exercise on upper limb function among stroke patients. Trial registration ClinicalTrials.gov Chi CTR 2400085317